A Study on Ambivalent Characteristics on the Consume Behavior Satisfaction of Korean University Students based on Smartphone User Observation - Ran Lee, Mi (International Journal of Engineering and Technology, 2019)
Along with the survey result that Korean’s mobile search rate is the highest in the world, the strengths such as effectiveness, achievement and convenience and the weak points such as dependence, loss of control, alienation influence the quality of our lives significantly.This study is to diagnose the consume behavior on smart phone use by students, to draw the elements, to figure out the characteristic of smart phone and mobile consumption on the life satisfaction of Korean college students. The questionnaires method was carried out for 200 college students who reside in metropolitan area and the observation method and focus group interview were carried out for 20 persons. As a result of analysis, it was analyzed into the form of leisure activities and relationships, learning activities, the focus group interview showed the advertise of mobile shopping highly induces impulse buying, in particular, the education to prevent mobile impulse buying is needed for female college students. Conclusively, the development of consumer sovereignty recovery project, smart consumption contents development and education, customized service for female college students must be developed complexly; it has the meaning of study as a basic data for future oriented youth policy and social welfare policy development.